Macronyssus crosbyi - Orlova, M. V.; Klimov, P. B.; Orlov, O. L.; Smirnov, D. G.; Zhigalin, A. V.; Budaeva, I. V.; Emelyanova, A. A.; Anisimov, N. V. (Zenodo, 2021)
Macronyssus crosbyi (Ewing & Stover, 1915) Liponyssus crosbyi Ewing & Stover, 1915: 109. Leiognathus crosbyi .— Ewing, 1923: 7. Ichoronyssus hasei Vitzthum, 1932: 23 (synonymy by Radovsky, 1966). Ichoronyssus kolenatii Fonseca, 1948: 280 (synonymy by Radovsky, 1966). Ichoronyssus crosbyi .— Fonseca, 1948: 299; Yunker & Radovsky, 1966: 98. Ichoronyssus britanicus .— Furman, 1950: 480 (misidentification). Ichoronyssus quadridentatus Strandtmann & Hunt, 1951: 462; Baker & Strandtmann, 1959: 225 (synonymy by Radovsky, 1966). Macronyssus crosbyi .— Radovsky, 1966: 94; 1967: 119; Anciaux de Faveaux, 1971: 52; Hoffmann et al ., 1972: 153; Whitaker, 1973: 1149; Yunker et al ., 1975: 252; Whitaker et al ., 1983; Whitaker & Maser, 1985: 73; Stanjukovich, 1990: 197; Ritzi et al ., 2001: tabl.; Reeves et al ., 2007: 53; Jaunbauere et al ., 2008: 40; Radovsky, 2010: 56. Type locality: Rockport, Missouri (Ewing & Stover, 1915). Type host: “ Vesper subulatus ” (Ewing & Stover, 1915). Material. M ex soprano pipistrelle Pipistrellus pygmaeus Leach, 1825 from biological station “Venevitinovo”, 4 June 2019, leg. O.L. Orlov, I. V. Budaeva. Distribution in Russian Federation: Karelia Republic (Lebedeva et al ., 2020), Voronezh Province (present paper), Krasnoyarsk Region (Orlova et al ., 2017a), Irkutsk Province (Orlova et al ., 2017a), Buryatiya Republic (Orlova et al ., 2017a), Yakutiya Republic (Orlova et al ., 2017a), Khabarovsk Region (Medvedev et al ., 1991), Magadan Province (Medvedev et al ., 1991), [Urals, Altai, Russian Far East— Orlova et al ., 2015d]. Distribution outside Russian Federation: Europe (Baltic states— Stanyukovich, 1990a; Jaunbauere et al ., 2008), North and South America (Radovsky, 1967; Hoffmann et al ., 1972; Presley 2004). Hosts (Old World): Eptesicus nilssonii (Stanyukovich, 1990a; Lebedeva et al ., 2020), Myotis daubentonii (Stanyukovich, 1990a), M . dasycneme (Stanyukovich, 1990a), M . mystacinus (Stanyukovich, 1990a), M . sibiricus (Orlova et al ., 2017a), M . brandtii (Stanyukovich, 1990a), Pipistrellus nathusii (Stanyukovich, 1990a), Pipistrellus pygmaeus (present paper), Vespertilio murinus (Stanyukovich, 1990a), Plecotus ognevi (as Pl . auritus ) (Medvedev et al ., 1991). : Published as part of Orlova, M. V., Klimov, P. B., Orlov, O. L., Smirnov, D. G., Zhigalin, A. V., Budaeva, I. V., Emelyanova, A. A. & Anisimov, N. V., 2021, A checklist of bat-associated macronyssid mites (Acari: Gamasina: Macronyssidae) of Russia, with new host and geographical records, pp. 537-564 in Zootaxa 4974 (3) on pages 544-545, DOI: 10.11646/zootaxa.4974.3.4, http://zenodo.org/record/4778060 : {"references": ["Ewing, H. E. & Stover, A. J. (1915) New parasitic mites (Acarina). Entomological News, 26, 109 - 114.", "Ewing, H. E. (1923) The Dermanyssid mites of North America. Proceedings of the United States National Museum, 62, 1 - 26. https: // doi. org / 10.5479 / si. 00963801.62 - 2459.1", "Vitzthum, H. (1932) Neue parasitische Fledermausmilben aus Venezuela. Zeitschrift fur Parasitenkunde, 4, 1 - 47. https: // doi. org / 10.1007 / BF 02122048", "Radovsky, F. (1966) Revision of the macronyssid and laelapid mites of bats: outline of classification with descriptions of new genera and new type species. Journal of Medical Entomology, 3, 93 - 99. https: // doi. org / 10.1093 / jmedent / 3.1.93", "Fonseca, F. da (1948) A monograph of the genera and species of Macronyssidae Oudemans, 1936 (synom: Liponissidae Vitzthum, 1931) (Acari). Proceedings of the Zoological Society of London, 118, 249 - 334. https: // doi. org / 10.1111 / j. 1096 - 3642.1948. tb 00378. x", "Yunker, C. E. & Radovsky, F. J. (1966) The Dermanyssid Mites of Panama (Acarina: Dermanyssidae). In: Wenzel, R. L. & Tipton, V. J. (Eds.), Ectoparasites of Panama. Field Museum of Natural History, Chicago, Illinois, pp. 83 - 103.", "Furman, D. P. (1950) New mites (Acarina: Liponyssinae) from North American bats. Journal of Parasitology, 36, 479 - 484. https: // doi. org / 10.2307 / 3273176", "Strandtmann, R. W. & Hunt, O. E. (1951) Two new species of Macronyssidae, with notes on some established genera (Acarina). Journal of Parasitology, 37, 460 - 470. https: // doi. org / 10.2307 / 3273253", "Baker, E. W. & Strandtmann, R. W. (1959) Further notes on Ichoronyssus quadridentatus Strandtmann and Hunt, with a description of the female. Proceedings of the Entomological Society of Washington, 61, 225 - 228.", "Radovsky, F. (1967) The Macronyssidae and Laelapidae (Acarina: Mesostigmata) parasitic on bats. University of California, Berkeley, California, 288 pp.", "Anciaux de Faveaux, M. (1971 - 1985) Catalogue des Acariens parasites et commensaux des Chiropteres. Institut royal des sciences naturelles de Belgique, Documents du travail, 7 (1, 6 & 7 Partie), 1 - 91, 452 - 546 & 547 - 637.", "Whitaker, J. O. Jr. (1973) External parasites of Bats in Indiana. Journal of Parasitology, 59, 1148 - 1150. https: // doi. org / 10.2307 / 3278665", "Yunker, C. E., Brennan, J. M., Hughes, L. E., Philip, C. B., Clifford, C. M., Peralta, P. H. & Vogel, J. (1975) Isolation of viral and rickettsial agents from Panamanian Acarina. Journal of Medical Entomology, 12, 250 - 255. https: // doi. org / 10.1093 / jmedent / 12.2.250", "Whitaker, J. O. Jr., Yunker, C. E. & Maser, C. (1983) Acarine ectoparasites (mites) of bats of Oregon. Northwest Science, 57, 97 - 106.", "Whitaker, J. O. & Maser, C. (1985) Mites (excluding chiggers) of mammals of Oregon. Great Basin Naturalist, 45, 67 - 74.", "Stanjukovich M. K. (1990 b) [The new species Macronyssus evansi (Parasitiformes, Gamasina) from bats]. Parasitologiya, 24, 71 - 73. [in Russian]", "Ritzi, Ch. M., Ammerman, L. K., Dixon, M. T. & Richerson, J. V. (2001) Bat ectoparasites from the Trans-Pecos region of Texas, including notes from Big Bend National Park. Journal of Medical Entomology, 38 (3), 400 - 404. https: // doi. org / 10.1603 / 0022 - 2585 - 38.3.400", "Reeves, W. K., Durden, L. A., Ritzi, Ch. M., Beckham, K. R., Super, P. E. & O'Connor, B. M. (2007) Ectoparasites and other ectosymbiotic arthropods of vertebrates in the Great Smoky Mountains National Park, USA. Zootaxa, 1392 (1), 31 - 68. https: // doi. org / 10.11646 / zootaxa. 1392.1.2", "Jaunbauere, G., Salmane, I. & Spungis, V. (2008) Occurence of Bat Ectoparasites in Latvia. Latvijas Entomologi, 45, 38 - 42.", "Radovsky, F. (2010) Revision of Genera of the parasitic mite family Macronyssidae (Mesostigmata: Dermanyssoidea) of the world. Indira Publishing House, West Bloomfield, Michigan, 170 pp.", "Lebedeva, D. I., Belkin, V. V., Stanyukovich, M. K., Bespyatova, L. A. & Bugmyrin, S. V. (2020) First records of bat parasites in Karelia. Transactions of the Karelian Research Centre of the Russian Academy of Sciences, 8, 120 - 125. https: // doi. org / 10.17076 / bg 1142", "Orlova, M. V., Kazakov, D. V., Kravchenko, L. B. & Zhigalin, A. V. (2017 a) Ectoparasite fauna of the Siberian bat Myotis sibiricus (Chiroptera: Vespertilionidae) with a revision of previous data on ectoparasites from Brandt's bat Myotis brandtii s. l. and the whiskered bat M. mystacinus s. l. of the Eastern Palaearctic. Entomological Review, 97, 1166 - 1173. https: // doi. org / 10.1134 / S 0013873817080164", "Medvedev, S. G., Stanyukovich, M. K., Tiunov, M. P. & Farafonova, G. V. (1991) [Ectoparasites of bats of the Russian Far East]. Parazitologiya, 25, 27 - 37. [in Russian]", "Orlova, M. V., Stanyukovich, M. K. & Orlov, O. L. (2015 d) Gamasid mites (Mesostigmata: Gamasina) associated with bats (Chiroptera: Vespertilionidae, Rhinolophidae, Molossidae) of boreal Palaearctic zone (Russia and adjacent countries). Publishing House of Tomsk State University, Tomsk, 150 p\u0440.", "Stanyukovich, M. K. (1990 a) [Gamasid and Argasidae mites of bats of Baltic states and Leningradskaya oblast]. Parazitologiya, 24, 193 - 199. [in Russian]"]}